A-cluster points via ideals - Gurdal, M.; Savaş, E. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Following the line of the recent work by Sava¸s et al., we apply the notion of ideals to A-statistical cluster points. We get necessary conditions for the two matrices to be equivalent in a sense of A^I -statistical convergence. In addition, we use Kolk’s idea to define and study B^I -statistical convergence.